PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEB DENGAN FRAMEWORK LARAVEL (STUDI KASUS PADA DIREKTORAT SARANA PRASARANA UNIVERSITAS KRISTEN MARANATHA) - Arvanullah; Rina Kurniawati (INFOKOM (Informatika & Komputer), 2024)
This research aims to design and develop a web-based inventory information system using the waterfall method, utilizing Unified Modeling Language (UML) for visual modeling to comprehend the involved business processes. Data collection techniques in this study were obtained through field observations, user interviews, and literature reviews. The implementation of this information system is carried out using the PHP web programming language with the Laravel framework, aiming to control inventory, monitor transactions, and present more accurate and rapid data reports. Previously, the Directorate of Infrastructure at Maranatha Christian University used manual methods and processes in managing inventory. The research results indicate that the effective use of web-based information systems can enhance efficiency and accuracy in inventory management. Thus, this research provides a solution that facilitates inventory management and improves operational efficiency in daily activities.